Analysis of the Influence of Work Discipline and Work Motivation on the Performance of ASN Employees with Work Commitment as an Intervening Variable in Medan City Education Office - Zhuraina; Kiki Farida Ferine (CV. Doki Course and Training, 2026)
This study aims to analyze the influence of work discipline and work motivation on the performance of State Civil Apparatus (ASN) employees with work commitment as an intervening variable in the Medan City Education Office. The main problem in this study is the lack of optimal employee performance which is allegedly influenced by various levels of discipline and work motivation. The research method used is a quantitative approach with survey techniques through the distribution of questionnaires to ASN employees. The data was analyzed using the path analysis method or Structural Equation Modeling (SEM) to test the direct and indirect influence between variables. The results of the study show that work discipline and work motivation have a positive and significant effect on work commitment. Work discipline and work motivation also have a positive and significant effect on employee performance. In addition, work commitment has been proven to be able to mediate the influence of work discipline and work motivation on employee performance significantly. These findings confirm that the improvement of ASN performance is not only determined by discipline and motivation aspects, but also by the level of commitment of employees to the organization. This research provides practical implications for the management of the Medan City Education Office in formulating performance improvement policies based on strengthening discipline, motivation, and work commitment.